Severe respiratory distress secondary to pharyngeal perforation during endoscopic gastrostomy tube removal: a clinical case report - Siblani, Dima; Stiel, Laure; Husson-Wetzel, Stéphanie; Barsotti, Pierre (Frontiers in Gastroenterology, 2023)
We present the case of a 60-year-old patient with advanced chronic obstructive pulmonary disease (COPD), who presented for planned endoscopic removal of her gastrostomy feeding tube, which was inserted for nutritional status optimization prior to lung transplantation. The procedure was complicated by accidental blockage of the device at the pharyngeal level, causing a transmural laceration. Rapid respiratory distress developed with subcutaneous emphysema that led to the intubation of the patient. A new endoscopic retrieval was attempted but failed, and the patient was sent to the operating room after a cervical and thoracic CT scan that showed the blocked piece in the cervical wall, in addition to diffuse subcutaneous emphysema, a large pneumomediastinum, and a left pneumothorax. The surgery consisted of a left cervicotomy, a pharyngeal incision, and retrieval of the trapped parts. The patient was sent to the intensive care unit (ICU) where she could be weaned and extubated 1 week later.